2022
DOI: 10.1111/pce.14409
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the complicated networks contribute to adventitious rooting in transgenic MdWOX11 apple microshoots under nitrate treatments

Abstract: Adventitious root formation is a bottleneck for the mass propagation of microshoots, and nitrate is an essential nutrient regulating adventitious roots. WOX11 is involved in adventitious rooting. But the crosstalk between nitrate and WOX11 is completely unknown. In this study, MdWOX11 transgenic apple microshoots were grown on different nitrate treatments. Low nitrate promotes adventitious rooting in overexpressed microshoots more than wild type and RNA interference microshoots. In contrast, medium nitrate sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…The estimated tolerance limit of 35S:WOX11-SRDX plants for cyst nematode infections was substantially lower than that of wild-type Col-0 plants. Others have shown that homologs of Arabidopsis WOX11 in rice, apple ( Malus ), and poplar enhance plant tolerance to abiotic stresses, such as drought and low nitrate conditions, by regulating adventitious lateral root formation ( Cheng et al 2016 ; Wang et al 2020 , 2021 ; Tahir et al 2022 ). Furthermore, WOX11 functions as a key regulator in the regeneration of primary roots after mechanical injury by inducing the formation of adventitious lateral roots at the cut site ( Sheng et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The estimated tolerance limit of 35S:WOX11-SRDX plants for cyst nematode infections was substantially lower than that of wild-type Col-0 plants. Others have shown that homologs of Arabidopsis WOX11 in rice, apple ( Malus ), and poplar enhance plant tolerance to abiotic stresses, such as drought and low nitrate conditions, by regulating adventitious lateral root formation ( Cheng et al 2016 ; Wang et al 2020 , 2021 ; Tahir et al 2022 ). Furthermore, WOX11 functions as a key regulator in the regeneration of primary roots after mechanical injury by inducing the formation of adventitious lateral roots at the cut site ( Sheng et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, no data on WOX11 orthologs inducing SE or shoot regeneration have been published; however, they were shown to induce rooting and callus development [ 10 ]. On the other hand, MdWOX11 overexpression was shown to repress shoot regeneration in Malus domestica [ 7 ]. Since the expression of MtWOX11-1 increases during SE [ 13 ], it prompts finding the functions of this gene in this process, probably using mutant analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the WOX11 pathway results in decreased rooting ability, whereas overexpression of WOX11 increases the ability of detached leaves to form roots [ 3 ]. The regulation of adventitious root initiation in leaves or in damaged roots by the WOX11 transcription factor or its orthologs has been studied in many species, including Panax [ 6 ], Malus [ 7 ], Populus [ 8 ], and Oryza [ 9 ] genera. In Panax ginseng adventitious roots branching regulation, WOX11 ortholog was shown to be a part of WOX-CLAVATA regulatory loop with the PgCLE45 gene.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated tolerance limit of 35S:WOX11-SRDX plants for cyst nematode infections was significantly lower than for wild-type Col-0 plants. Others have shown that homologs of Arabidopsis WOX11 in rice, apple, and poplar enhance plant tolerance to abiotic stresses, such as drought and low nitrate conditions, by regulating adventitious lateral root formation (Cheng et al, 2016;Wang et al, 2020;Wang et al, 2021;Tahir et al, 2022). Furthermore, WOX11 functions as a key regulator in the regeneration of primary roots after mechanical injury by inducing the formation of adventitious lateral roots at the cut site (Sheng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%